Bleeding disorders, longer operative time, and nongeneral anesthesia increase are associated with overnight admission after hip arthroscopy - Zhong, Jack; Crutchfield, Connor R; Lee, Nathan J; Mueller, John; Ahmad, Christopher; Trofa, David; Lynch, Thomas Sean (Journal of hip preservation surgery, 2025)
Abstract Overnight admission is a rare but major complication after hip arthroscopy (HA), and the paucity of data surrounding its causes limits patient education and quality of care. The purpose of this study was to identify risk factors for an unanticipated overnight admission after HA and assess for associated complications. This analysis queried the American College of Surgeons National Surgical Quality Improvement Program database using Current Procedural Terminology codes to identify hip arthroscopies from 2005 to 2017. Patient demographics, perioperative variables, and comorbidities were compared between ambulatory and nonambulatory patients [length of stay (LOS) ≥ 1] using bivariate analysis. Multivariate stepwise logistic regression then identified independent risk factors of adverse outcomes. Linear regression analyzed correlation of LOS with age, operative time, modified fragility index (mFI-5), and year of operation. A total of 2420 cases were included in this study with 400 (16.5%) overnight admissions. The mean subject age was 40 ± 13.9 years old (58.1% female). Admitted patients generally had higher American Society of Anesthesiologists (ASA) scores and a higher mFI-5 index. Multivariate logistic regression showed that mFI-5 > 0, bleeding disorders, operative time >1.5 h, and nongeneral anesthesia were independent risk factors for prolonged hospital stay. Patients aged 31–40 years had decreased risk of LOS ≥1. Nonambulatory surgery was associated with significantly increased risk for any complication, readmission, wound complication, and venous thromboembolism. This analysis demonstrates that operations >1.5 h and increased medical comorbidities predispose patients to greater risk of being admitted to the hospital after HA. Surgeons should consider these data to optimize controllable factors and patient selection to reduce the risk of postoperative admission.